Effects of melamine and cyanuric acid on renal function and structure in rats - Saranya Peerakietkhajorn,; Nawiya Huipao,; Siriphun Hiranyachattada, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Melamine has been used to increase the amount of measurable nitrogen which is a component of protein. The renal toxicity of melamine has been reported in infants and animals that consumed a mixture of melamine in their food products. This study aimed to investigate the effects of melamine on rat renal function using clearance and histological techniques. Animals were divided into 3 groups: vehicle control, 400 mg/kg melamine and mixture of 400 mg/kg melamine and 400 mg/kg cyanuric acid (p.o., daily for three days). The results showed that blood urea nitrogen level significantly increased in the rats treated with the mixture of melamine and cyanuric acid. The urine flow rate, glomerular filtration rate, renal plasma flow and urinary sodium and potassium excretion rate significantly decreased when compared to vehicle control. These results suggested both glomeruli and renal tubules of rats treated with mixture of melamine and cyanuric acid were damaged. Histological study also confirmed these findings and showed significant glomerular atrophy and dilated renal tubules. Numerous clear brownish-yellow crystals were also found in the distal tubule, collecting tubule and papillary duct. However, rats solely treated with melamine showed no significant difference in renal function or structures.